IMPLEMENTASI DIGITAL MARKETING SEBAGAI STRATEGI PEMASARAN GUNA MENINGKATKAN DAYA SAING UMKM DI INDONESIA - Elvri Ranjani; Muhammad Iqbal Fasa; Is Susanto (PT. Intelek Cendikiawan Nusantara, 2024)
Technology continues to evolve in modern life. The internet allows everyone to access information quickly and easily without time or space restrictions. This opens up opportunities for small and medium enterprises (MSMEs) to use it to market their goods. The purpose of this study is to identify and analyze the importance of implementing digital marketing as an effective marketing strategy for MSMEs to improve their competitiveness in the market. This research is expected to help MSMEs in improving their marketing visibility, efficiency and effectiveness as well as building better relationships with consumers. The study utilizes qualitative methodology, critical discussion from the author's point of view, as well as support for literature searches, quotes, expert opinions, and previous findings on the subject. The results show that digital advertising increases the sales of MSMEs. In addition, this study shows that while there are many benefits to be gained from using digital advertising, MSME players are often faced with various challenges. The author hopes that MSME players in Indonesia can continue to innovate and develop their businesses without ignoring technological developments. The government is also expected to be complementary to encourage various efforts that have been made by MSMEs to improve their competitiveness.